The significance of the tail projections in female entomopathogenic nematodes within the family Steinernematidae - Mráček, Z; Půža, V; Nermut', J (Journal of helminthology, 2016)
Several taxonomic studies of the entomopathogenic nematode family Steinernematidae have reported on the minute tail projections on the tail tips of females of the first generation; however, the occurrence and morphology of these traits in other steinernematid species and their taxonomic significance are still unclear. In the present study, the tail projections in females of seven steinernematid species belonging to four phylogenetic clades were examined. The projections are present in all of the tested species and their number and shape is consistent within species but significantly differs among species. It thus seems that these structures may have taxonomic significance at the species level. Based on these results, we suggest that every description of a new species in the family Steinernematidae should contain a precise morphology of the female tail, focused on these projections, using both light and scanning electron microscopy.
Keywords: hlístice; Animals; Female; Tail; ženské pohlaví; Nematoda; zvířata; ocas